2016
DOI: 10.1186/s12936-016-1297-3
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Plasmodium berghei transgenic parasite expressing the full-length Plasmodium vivax circumsporozoite VK247 protein for testing vaccine efficacy in a murine model

Abstract: BackgroundThe approach of using transgenic rodent malaria parasites to assess the immune system’s response to antigenic targets from a human malaria parasite has been shown to be useful for preclinical evaluation of new vaccine formulations. The transgenic Plasmodium berghei parasite line [PvCSP(VK210)/Pb] generated previously expresses the full-length circumsporozoite protein (CSP) VK210 from Plasmodium vivax. The transgenic parasite expresses one of the two most common alleles of CSP, defined by nine amino a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…The role played by low complexity regions within Plasmodium species is debated. Evidence from previous studies have supported either a neutral or functional role of these regions based on experimental and computational analyses of regions primarily in Plasmodium falciparum and few other selected species and strains 10 , 20 , 23 , 41 43 . A more comprehensive evolutionary approach has the potential to clarify the role played by LCRs in relation to phenotypic variability by adding information on the history of these regions through time.…”
Section: Discussionmentioning
confidence: 98%
“…The role played by low complexity regions within Plasmodium species is debated. Evidence from previous studies have supported either a neutral or functional role of these regions based on experimental and computational analyses of regions primarily in Plasmodium falciparum and few other selected species and strains 10 , 20 , 23 , 41 43 . A more comprehensive evolutionary approach has the potential to clarify the role played by LCRs in relation to phenotypic variability by adding information on the history of these regions through time.…”
Section: Discussionmentioning
confidence: 98%
“…b Salivary gland sporozoite no. b Reference; RMgmDB ID c Remarks (mutation, sporozoite phenotype) Chimeric CSP parasite lines P. berghei Py CSP WT WT [ 44 ]; 75 P. berghei Pf CSP WT Reduced (90%) [ 52 ]; 69 P. berghei Pf CSP WT Reduced (90%) 342 P. berghei Pf CSP WT WT [ 53 ]; 4110 P. berghei Pf CSP WT WT [ 54 ]; 4135 P. yoelii Pf CSP WT WT [ 55 ]; 1442 P. berghei Pv CSP-210 WT WT [ 27 ]; 4136 P. berghei Pv CSP-247 WT WT [ 28 ]; 1443 P. berghei Pv CSP-247 WT …”
Section: Resultsmentioning
confidence: 99%
“…The lack of complete functional complementation was unexpected, since chimeric rodent Plasmodium berghei parasites expressing Pv CSP-VK210 and Pv CSP-VK247 are able to produce salivary gland sporozoites in An. stephensi mosquitoes that are infective to mice [ 27 , 28 ]. The findings in this study and the species-specific features of CSP that may govern full maturation and development of sporozoites of the two human malaria-parasite species are discussed.…”
Section: Introductionmentioning
confidence: 99%
“…While previous studies using intravenously inoculated sporozoites demonstrated that P. yoelii sporozoites develop better in the liver compared to P. berghei (16)(17)(18)(19), our results suggest that the higher infectivity of P. yoelii sporozoites is also due to their behavior in the skin, further supporting the notion that sporozoite motility in the dermis is a valid correlate for infectivity of the parasite. Recently a number of transgenic rodent parasite lines expressing P. falciparum or P. vivax CSP have been developed for pre-clinical vaccine testing in the rodent model (27)(28)(29). The different biology of the two rodent malaria species could impact the interpretation of antibody-based interventions performed in the rodent model and should be considered when evaluating vaccine candidates targeting sporozoites.…”
Section: Discussionmentioning
confidence: 99%